The Relation of Academic Strees to Intensity of Playing Online Games - Rizki Agusman; Marjohan Marjohan (Jurnal Neo Konseling, 2019)
Education carried out today faces many problems and obstacles, including the influence of increasingly rapid and advanced technology. The invention of information technology is developing on a mass scale. Technology has changed the shape of society, from the local world community to the global world community. In the task of adolescent development, the tendency of adolescents should be able to achieve emotional independence and socializing with peers and the opposite sex, but the reality on the ground there are still many teenagers who have not been able to achieve these developmental tasks. In the learning process many teenagers who feel unable to face the academic demands they find in the world of education and experience stress, most of them relieve stress by playing online games. It is hoped that in this study, students improve the management of academic stress that is still poor and understand the impact of playing online games. Counseling teachers are expected to be able to provide input for schools to develop a counseling program in developing steps to prevent the occurrence of academic stress experienced by students, as well as making preventive efforts to the intensity of students in playing online games. The next researcher is expected to study and research more about academic stress and the intensity of playing online games by taking different aspects, as well as a larger number of samples.This type of research is classified as correlational descriptive. The population of this study is the students of SMA PGRI 2 Padang in the academic year 2019/2020 with 180 students with a sample of 64 students. The data collection tool used was a questionnaire. Data analysis techniques used the Pearson Product Moment formula with the help of the Statistical Product and Service Solution for Windows version 20 program. The research findings show that (1) the level of academic stress of SMA PGRI 2 Padang students is in the medium category, (2) The level of intensity in playing online games of PGRI 2 Padang high school students is in the moderate category, (3) There is a significant relationship between academic stress and intensity play online games for high school students of PGRI 2 Padang with Pearson correlation 0.532 and a significant level of 0.000 with a fairly strong relationship level.